Physicochemical Properties and Pesticide Residues in Okra Fruits (Abelmoschus esculentus L.) (Dhaka University Journal of Science, 2020)
Vegetable acts as major valuable source of nutrients. Among different vegetables, okra was analyzed to study moisture content, ash content, soluble dietary fiber (SDF), total carbohydrates, and micro-minerals, fatty acid compositions and pesticide residues. Fatty acid compositions were studied by gas chromatograph equipped with a flame ionization detector (GC-FID) while, gas chromatograph equipped with electron capture detector GC-ECD was used for analysis of pesticide residues. Total carbohydrate content was determined by ultraviolet-visible spectrophotometer. The amount of soluble dietary fiber was estimated by acid extraction method. Fe, Cu and Zn content were analyzed by atomic absorption spectroscopy (AAS). The relative percentage of fatty acids were found to be palmitic, cis-9-oleic, linoleic, linolenic and arachidic acid in a range of 0.27-1.35, 3.78 - 6.32, 30.67- 38.44, 2.13 - 4.85 and 1.29 -3.17 %, respectively. Residual diazinon, chlorpyrifos, fenvalerate, cypermethrin and quinalphos were not found to be present in any sample. Total carbohydrate, SDF, moisture and ash content in fresh okra fruits were found to be 6.01- 6.09, 3.35 - 3.50, 88.02 - 91.84 and 1.72 - 2.04 %, respectively. The amount of Fe, Cu and Zn was 11.41-11.43, 1.78 -1.85 and 8.56 - 9.05 mg per 100 g sample, respectively.Dhaka Univ. J. Sci. 68(2): 155-160, 2020 (July)